2021
DOI: 10.3389/fpls.2021.734419
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Micro Ribonucleic Acids and Their Targets in Response to Plasmodiophora brassicae Infection in Brassica napus

Abstract: Clubroot disease, which is caused by the soil-borne pathogen Plasmodiophora brassicae War (P. brassicae), is one of the oldest and most destructive diseases of Brassica and cruciferous crops in the world. Plant microRNAs [micro ribonucleic acids (miRNAs)] play important regulatory roles in several developmental processes. Although the role of plant miRNAs in plant-microbe interaction has been extensively studied, there are only few reports on the specific functions of miRNAs in response to P. brassicae. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 95 publications
2
12
0
Order By: Relevance
“…Differential expression from targets of the aforementioned miRNA families was observed in our studies during seed development, and further target validation through degradome sequencing (German et al, 2008), precise isomiRs classification (Morin et al, 2008; Sablok et al, 2015; Yang et al, 2019), target knock-out experiments (Jain et al, 2018; Wei et al, 2018; Li et al, 2021) as well as gene co-expression networks (Schiessl et al, 2020) can prove beneficial for identifying their role in seed and embryo formation in B . napus .…”
Section: Discussionmentioning
confidence: 70%
“…Differential expression from targets of the aforementioned miRNA families was observed in our studies during seed development, and further target validation through degradome sequencing (German et al, 2008), precise isomiRs classification (Morin et al, 2008; Sablok et al, 2015; Yang et al, 2019), target knock-out experiments (Jain et al, 2018; Wei et al, 2018; Li et al, 2021) as well as gene co-expression networks (Schiessl et al, 2020) can prove beneficial for identifying their role in seed and embryo formation in B . napus .…”
Section: Discussionmentioning
confidence: 70%
“…The miR172/TOE1-TOE2 is an important regulatory module in plants, involved in plant development regulation, morphogenesis and innate immunity (Zou et al, 2018;Werner et al, 2021). There has been reported that this module in response to P. brassicae infection in B. napus (Li et al, 2021a). In summary, the exploration of the CR mechanism involving ERF034 can be carried out from these three aspects: (i) hormone regulation associated with ERF034, including ethylene, SA, jasmonic acid (JA), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Novel miRNAs were identified in the differentially regulated set of another important crop plant, Chinese cabbage ( B. rapa ) using similar experimental approaches [ 108 ]. Extending these findings to resistant and susceptible cultivars of B. napus to P. brassicae identified several specific miRNA–target RNA pairs for the resistant reaction [ 109 ]. Consequently, specific miRNAs were identified that regulate disease tolerance genes of the TIR-NBS family in B. napus [ 110 ].…”
Section: Transcriptome and Posttranscriptional Regulationsmentioning
confidence: 99%